The SIESTA method; developments and applicability - Artacho, E.; Anglada, E.; Dieguez, O.; Gale, Julian; Garca, A.; Junquera, J.; Martin, R.; Ordejn, P.; Pruneda, J.; Sanchez-Portal, D.; Soler, J. (IOP Publishing Ltd, 2008)
Recent developments in and around the SIESTA method of first-principles simulation of condensed matter are described and reviewed, with emphasis on (i) the applicability of the method for large and varied systems, (ii) efficient basis sets for the standards of accuracy of density-functional methods, (iii) new implementations, and (iv) extensions beyond ground-state calculations.